Synthesis, Spectroscopic Characterization and in Vitro Cytotoxicity Assay of Mropholine Mannich Base Derivatives of Benzimidazole with Some Heavy Metals - Alias, Mahasin; Bakir, Shaimaa R (Al-Nahrain Journal of Science, 2018)
Mannich bases derivatives of Benzimidazole were prepared from condensation reaction of 2-mercaptobenzimidazole with formaldeyhed once with mropholine and another with pyrazinamide to prepare L1 and L2 respectively, coordinated with three metal ions of Pd(II), Pt(IV) and Au(III). The structures of these compounds were confirmed by metal and elemental analyses, UV-Vis and FT-IR spectroscopy, magnetic susceptibility, conductivity measurement at room temperature, 1HNMR and 13CNMR. Experimental results showed that the ligands (L1&L2) coordinated as bi-dentate and tridentate with metal ions respectively. Cytotoxicity of Mannich bases and their metal complexes were examined against mice cell line RAW 264.7 using MTT method .Each cell line was injected by following doses (400,200,100 and 50) µg/ml of prepared compounds by using mice cell as a negative control and cis-platin as a positive control. The ligands and Pd(II), Pt(IV), Au(III) complexes showed good activity at various concentrations especially Pd(II) complexes of both complexes.